2007
DOI: 10.1111/j.1365-2125.2006.02802.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of requests for serum digoxin concentrations: experience from an Australian Regional Health Service

Abstract: What is already known about this subject • Therapeutic drug monitoring of serum digoxin concentrations (SDC) is considered useful in enhancing the therapeutic benefits of digoxin and minimizing the incidence of adverse drug reactions. • The quality of requests for SDC has been reported to be generally unsatisfactory. However, studies have focused on few information parameters. • A better knowledge of these issues might be useful to target appropriate areas of weakness within heathcare systems. What this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…Some caregivers are unaware that digoxin samples should be taken at least 6 hours after dosing and are confused by choices of multiple blood collection times (Matzuk et al, 1991;Bernard et al, 1996), the Fudan Children's Hospital has two main blood collection times, 13:30 and 15:00, and a common error is to reverse the timing. What's more, our study findings showed that the quality of requests was generally poor (Table 6), in fact, not a single digoxin therapeutic monitoring request had all the information codes required, this make hard for the pharmacists to correct the errors, another study reported similar findings (Ellington et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
“…Some caregivers are unaware that digoxin samples should be taken at least 6 hours after dosing and are confused by choices of multiple blood collection times (Matzuk et al, 1991;Bernard et al, 1996), the Fudan Children's Hospital has two main blood collection times, 13:30 and 15:00, and a common error is to reverse the timing. What's more, our study findings showed that the quality of requests was generally poor (Table 6), in fact, not a single digoxin therapeutic monitoring request had all the information codes required, this make hard for the pharmacists to correct the errors, another study reported similar findings (Ellington et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
“…However, in clinical practice, TDM requests are often inadequate: many requests are inappropriately timed or omitted because the indication is unknown or not recognized. (Ellington et al, 2007) Clinical rules are part of 'the next generation' medication safety systems. Incorporated in a clinical decision support system (CDSS), clinical rules are able to continuously monitor all individual electronic patient data available in the electronic medical record (EMR).…”
Section: Resultsmentioning
confidence: 99%
“…This often tends to produce both over‐sampling and under‐interpretation of the results, and prescribers mostly implement therapeutic adjustments by trial and error. Data for formal dosage adjustments are often not recorded along with blood sampling [19]. Monitoring is insufficient in some therapeutic areas and exaggerated in others, and large numbers of tests requested by practitioners are of questionable usefulness.…”
Section: Necessary Improvementsmentioning
confidence: 99%
“…1 Most monitoring procedures have been devised and set up mainly, if not exclusively, on empirical grounds, without critical assessment of the underlying evidence and rationale [18].This often tends to produce both oversampling and under-interpretation of the results, and prescribers mostly implement therapeutic adjustments by trial and error. Data for formal dosage adjustments are often not recorded along with blood sampling [19].…”
Section: Necessary Improvementsmentioning
confidence: 99%